Quality of Life in Patients with Chronic Kidney Disease - Esterlita Ayu Putri Apriliani; Oda Debora; Emy Sutiyarsih; Elizabeth Yun Yun Vinsur (STIKes Patria Husada Blitar, 2023)
Chronic kidney disease results in decreased kidney function in filtering metabolic waste so patients must receive replacement therapy for kidney function, one of which is hemodialysis. Hemodialysis therapy aims to achieve optimal health and a better quality of life. This study aims to determine the relationship between compliance to hemodialysis therapy and the quality of life of chronic kidney disease patients. This type of research is a descriptive correlation with a cross-sectional design. The research sample was 106 respondents using a purposive sampling technique. Statistical test using SPSS statistics 29 with Spearman correlation test. The results showed a p-value of 0.438 > Î± 0.05 so it was concluded that there was no significant relationship between compliance with the quality of life of chronic kidney disease patients. The quality of life tends to be good in the majority of hemodialysis patients because there is positive family, social and environmental support so that patients feel that hemodialysis therapy is not a burden. Quality of life is influenced by 4 components, namely physical, psychological, social, and environmental. Compliance is included in one of the physical components where there are several other components and factors that can support the improvement of the quality of life of hemodialysis patients besides compliance